Application of emerging technologies for research support in Nigerian academic libraries: Trends, problems and prospects - Sophia Vivian Adeyeye; Taofeek Abiodun Oladokun (IASSIST Quarterly, 2023)
Academic libraries in the modern era are often asked to justify their existence in tertiary institutions by showing how the institution and society at large have benefited from the library services. One main area that librarians often point to is the research productivity of members of academic institutions. However, studies have shown that research productivity among Nigerian scholars is low, which means that academic libraries have to be more innovative in supporting researchers in their domains. Emerging technologies offer innovative ways of supporting research activities by providing tools and resources that streamline the research process and ensure proper visibility for research outputs of academic library clients. This article, which is based on a review of previous studies, explores various areas where academic libraries in Nigeria can apply emerging technologies, the likely challenges, and strategies that can be adopted to ensure sustainable use of emerging technologies in academic libraries. It has been found that emerging technologies can enhance existing library services and create new ones, such as data mining, data management, and scholarly communication, among others. However, although steps are being taken by academic librarians in Nigerian tertiary institutions to leverage technology in providing the needed support for researchers, the pace of technology adoption is still slow and the range of technologies being adopted is limited compared to available options.  This state of affairs has been attributed to challenges such as lack of infrastructure, librarians’ skills, and a negative attitude towards change. The study recommends a multidimensional approach to the application of emerging technologies in Nigerian academic libraries